Detection of Pathognomonic Biomarker PrP(Sc) and the Contribution of Cell Free-Amplification Techniques to the Diagnosis of Prion Diseases - Eraña, Hasier (Biomolecules, 2020)
Transmissible spongiform encephalopathies or prion diseases are rapidly progressive neurodegenerative diseases, the clinical manifestation of which can resemble other promptly evolving neurological maladies. Therefore, the unequivocal ante-mortem diagnosis is highly challenging and was only possible by histopathological and immunohistochemical analysis of the brain at necropsy. Although surrogate biomarkers of neurological damage have become invaluable to complement clinical data and provide more accurate diagnostics at early stages, other neurodegenerative diseases show similar alterations hindering the differential diagnosis. To solve that, the detection of the pathognomonic biomarker of disease, PrP(Sc), the aberrantly folded isoform of the prion protein, could be used. However, the amounts in easily accessible tissues or body fluids at pre-clinical or early clinical stages are extremely low for the standard detection methods. The solution comes from the recent development of in vitro prion propagation techniques, such as Protein Misfolding Cyclic Amplification (PMCA) and Real Time-Quaking Induced Conversion (RT-QuIC), which have been already applied to detect minute amounts of PrP(Sc) in different matrixes and make early diagnosis of prion diseases feasible in a near future. Herein, the most relevant tissues and body fluids in which PrP(Sc) has been detected in animals and humans are being reviewed, especially those in which cell-free prion propagation systems have been used with diagnostic purposes.